(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
This community service program aimed to introduce digital literacy and basic programming to junior high school students at SMP Al Azhar Syifa Budi Parahyangan, an A-accredited school lacking a formal ICT curriculum. The program utilized a Learning Management System (LMS) built with C++ programming exercises and auto-grading features to support digital learning. The LMS was enhanced based on an Iterative and Incremental Development (IID) approach. It was implemented through four face-to-face mentoring sessions conducted between February and May 2025. Program outputs included 231 coding problems, seven instructional videos, structured modules, interactive quizzes, and a Junior Coding Contest. Based on a survey of 11 respondents, 45.45% expressed satisfaction with the materials and mentoring. However, feedback highlighted challenges related to schedule and material complexity. Recommendations include integrating the program into formal class hours, using block-based programming tools such as Scratch, and involving teachers for sustainability. The project supports the goals of the Merdeka Curriculum and demonstrates that tailored LMS systems can be effective tools for digital education in schools with limited infrastructure.